Inhibition of metastasis and growth of breast cancer by pH-sensitive poly (β-amino ester) nanoparticles co-delivering two siRNA and paclitaxel. (April 2015) - Tang, Shan; Yin, Qi; Su, Jinghan; Sun, Huiping; Meng, Qingshuo; Chen, Yi; Chen, Lingli; Huang, Yongzhuo; Gu, Wangwen; Xu, Minghua; Yu, Haijun; Zhang, Zhiwen; et al.
Abstract: Breast cancer is the most vicious killer for women's health, while metastasis is the main culprit, which leads to failure of treatment by increasing relapse rate. In this work, a new complexes nanoparticles loading two siRNA (Snail siRNA (siSna) and Twist siRNA (siTwi)) and paclitaxel (PTX) were designed and constructed using two new amphiphilic polymer, polyethyleneimine-block-poly[(1, 4-butanediol)-diacrylate-β-5-hydroxyamylamine] (PEI-PDHA) and polyethylene glycol-block-poly[(1, 4-butanediol)-diacrylate-β-5-hydroxyamylamine] (PEG-PDHA) by self-assembly. The experimental results showed that in the 4T1 tumor-bearing mice models, PEI-PDHA/PEG-PDHA/PTX/siSna/siTwi) complex nanoparticles (PPSTs) raised the accumulation and retention of both PTX and siRNA in tumor after administrated intravenously, resulted in the strong inhibition of the tumor growth and metastasis simultaneously. It was found that co-delivery of siSna and siTwi had more significant anti-metastasis effect than delivering a single siRNA, as a result of simultaneously inhibiting the motility of cancer cells and degradation of ECM. Therefore, PPSTs could be a promising co-delivery vector for effective therapy of metastatic breast cancer.